2021
DOI: 10.1016/j.psj.2021.101417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stocking density on growth performance, feather quality, serum hormone, and intestinal development of geese from 1 to 14 days of age

Abstract: This study was conducted to investigate the effect of stocking density on growth performance, feather quality, serum hormone, and intestinal development of geese from 1 to 14 d of age. A total of 450 one-day-old geese were randomly allotted to 45 battery cage (0.65 m × 0.62 m) pens according to 5 stocking densities (15, 20, 25, 30, and 35 birds/m 2 ). The results showed that ADG and ADFI were reduced ( P < 0.05) as stocking density increased from 15 to 35 birds/m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The blood RBC, HGB, and HCT levels of chickens fed with Sihuang in the SH group increased, which improved the body's nutrient and oxygen transport capacity, and had a positive effect on the body's recovery. Under today's intensive and industrialized poultry production model, environmental stress will be an important cause of poultry intestinal and liver tissue damage [25][26][27]. The results of this study showed that feeding Sihuang significantly reduced the activities of ALT and AST enzymes in chicken serum, and could stabilize the ALT enzyme activities at the same level as in the CON group.…”
Section: Discussionmentioning
confidence: 65%
“…The blood RBC, HGB, and HCT levels of chickens fed with Sihuang in the SH group increased, which improved the body's nutrient and oxygen transport capacity, and had a positive effect on the body's recovery. Under today's intensive and industrialized poultry production model, environmental stress will be an important cause of poultry intestinal and liver tissue damage [25][26][27]. The results of this study showed that feeding Sihuang significantly reduced the activities of ALT and AST enzymes in chicken serum, and could stabilize the ALT enzyme activities at the same level as in the CON group.…”
Section: Discussionmentioning
confidence: 65%
“…The age of the birds had no effect on the quantity of down. The high stocking density could reduce the growth and impaired feather quality and intestinal development of geese ( Liu et al, 2021 ). Hamadani et al (2014) indicated an increasing trend of BW with the increase in age.…”
Section: Discussionmentioning
confidence: 99%
“…Goo et al [34] also reported that broilers reared under heat stress and high stocking density decreased performance with a negative impact on breast meat quality. During the starter period, studies have observed that high stocking density is associated with a reduction in feed intake and weight gain in White Pekin ducks [35] and geese [36]. Furthermore, research studies have provided scientific evidence that housing birds in a densely stocked environment can lead to elevated ambient temperatures surrounding the birds and lowering body heat dissipation resulting in heat stress conditions [33,37].…”
Section: Discussionmentioning
confidence: 99%